2013
DOI: 10.1111/jth.12258
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ compliance with the Padua Prediction Score for preventing venous thromboembolism among hospitalized medical patients

Abstract: To cite this article: Rossetto V, Barbar S, Vedovetto V, Milan M, Prandoni P. Physicians' compliance with the Padua Prediction Score for preventing venous thromboembolism among hospitalized medical patients. J Thromb Haemost 2013; 11: 1428-30.Hospitalization for acute medical illnesses confers an 8-fold increased risk of venous thromboembolic (VTE) disorders that persists for up to 3 months and is even higher after discharge than during in-hospital stay [1]. However, in spite of strong evidence in favor of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(18 reference statements)
1
8
0
1
Order By: Relevance
“…This is similar to the Italian study which showed most common risk factor was reduced mobility, advanced age, cardiac/respiratory failure and acute infection/rheumatological disorder. 14 Reduced mobility was the most common risk factor which might be due to our deeply rooted cultural practices that anyone who is admitted in hospital should take rest and lie in the bed most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the Italian study which showed most common risk factor was reduced mobility, advanced age, cardiac/respiratory failure and acute infection/rheumatological disorder. 14 Reduced mobility was the most common risk factor which might be due to our deeply rooted cultural practices that anyone who is admitted in hospital should take rest and lie in the bed most of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, it is inexperienced junior medical staff who assess patients and prescribe prophylaxis, and they would benefit from explicit and validated risk assessment models. Several models have been derived from large clinical databases (two are favoured by the ACCP), and although some have been partly validated, it remains likely that none will be very precise. Medical patient VTE prophylaxis remains a challenge because the benefit and risk of anticoagulant prophylaxis will differ between individuals, and because of the need to translate complex decision trees into routine clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent study, PPS demonstrated a good physicians' compliance: the awareness of the thrombotic risk-as assessed with the PPS-increased the rate of prescription of appropriate prophylaxis in high-risk medical patients from 39.6% of the previous study 29 up to 88.5% (p < 0.0001). 30 PPS was recommended by the ACCP guidelines in 2012 for VTE risk assessment in medical hospitalized patients. 15 The Geneva score and PPS have been prospectively validated in a cohort of 1,478 acutely ill medical patients enrolled in three academic and five nonacademic acute care hospitals in Switzerland.…”
Section: Main Vte Risk Scoring Systems In Medical Inpatientsmentioning
confidence: 99%